Method for improving high-temperature interface strength of quartz fiber reinforced resin-based composite material

By cleaning, activation and grafting the quartz fibers, the surface characteristics and interface bonding ability with the resin matrix are improved, and the problem of low interface strength of quartz fiber-reinforced resin-based composites under high temperature conditions is solved, and the high-temperature mechanical properties of the composites are significantly improved.

CN119550513AInactive Publication Date: 2025-03-04AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411725584.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Quartz fiber reinforced resin-based composites have low interfacial strength and are prone to damage under high temperature conditions, resulting in reduced mechanical properties and weak structural stability of the composites.

Method used

By cleaning, activation and grafting the quartz fibers, the surface roughness and specific surface area of ​​the fiber are improved, and the interface bonding ability with the resin matrix is ​​enhanced. Specific steps include chemical etching, grafting the silicone resin, and forming a high-temperature resistant silicone cured substance through post-treatment.

Benefits of technology

It effectively improves the high-temperature mechanical properties and interface bonding strength of quartz fiber reinforced resin-based composite materials, and enhances the high-temperature resistance and application value of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119550513A_ABST
    Figure CN119550513A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the high-temperature interface strength of a quartz fiber composite material. The method comprises the steps of fiber cleaning, fiber surface activating treatment, fiber surface grafting treatment and composite material forming. Taking the quartz fiber reinforced polyimide resin composite material as an example, the bending strength of the composite material prepared by the method is greater than or equal to 306Mpa under the test condition of 400 DEG C / 20min, and is improved by 43%; the interlayer shear strength is greater than or equal to 21.1 MPa and is improved by 35.2%, and the dielectric constant is less than or equal to 3.4. The method solves the problems of poor interface bonding strength, low mechanical strength and poor structural stability of the quartz fiber reinforced resin-based composite material under the long-time high-temperature working condition, and is simple, easy to operate and suitable for batch production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, relates to the preparation of fiber-reinforced resin-based composite materials, and specifically relates to a method for improving the high-temperature interface strength of quartz fiber-reinforced resin-based composite materials. Background Art

[0002] Resin-based wave-transparent composite materials are key structural and functional integrated composite materials. They are "transparent" to electromagnetic waves, ensuring smooth transmission of electromagnetic waves and reducing interface reflection and loss of electromagnetic waves. Based on the use requirements of special environments, resin-based wave-transparent composite materials are required to withstand temperatures of 500°C or even higher for a long time. Therefore, it is urgent to explore and study high-temperature resistant resin-based wave-transparent composite materials and their molding technology, break through the constraints in the preparation and molding of high-temperature resistant and high-performance resin-based wave-transparent composite materials, and lay a material foundation and technical support for the production and development of special wave-transparent functional products.

[0003] As a commonly used reinforcing material for resin-based wave-transparent composite materials, quartz fiber is widely used for its low dielectric, low loss, high strength, high modulus, high temperature resistance, and aging resistance. However, quartz fiber is made of 99.9% SiO2 through melt drawing. The fiber surface has high crystallinity and high chemical inertness. Therefore, the interfacial bonding strength with the resin matrix is ​​low, which affects the mechanical properties of the composite material. Therefore, a lot of research has been carried out on the surface modification of quartz fiber.

[0004] Tong Wenqing and others invented a method for preparing a modified quartz fiber / cyanate composite material, which includes the following steps: heat-treating the quartz fiber and then etching the surface to make uniform pits and gaps appear on its surface; surface grafting the etched quartz fiber to obtain surface-modified quartz fiber; using tetrahydrofuran as solvent to prepare a cyanate solution; immersing the surface-modified quartz fiber in the cyanate solution to obtain a modified quartz fiber / cyanate blend; drying the modified quartz fiber / cyanate blend to remove the tetrahydrofuran solvent, and then laminating and hot-pressing to prepare a modified quartz fiber / cyanate composite material. The modified quartz fiber / cyanate composite material prepared by this method has good heat resistance and high strength, high interface shear strength between the quartz fiber and the cyanate matrix, excellent mechanical properties and dielectric properties, and is widely used in aviation, aerospace, electronics and other scientific and technological fields.

[0005] Zhang Ling and others invented a method for preparing a composite material of epoxy resin reinforced with in-situ growth of carbon nanotubes on the surface of quartz fiber. The method treats the surface of quartz fiber with catalyst particles on the upper layer, uses chemical vapor deposition (CVD) to cause the catalyst to trigger the decomposition of carbon sources to generate carbon nanotubes, and prepares quartz fiber with a uniform carbon nanotube array on the surface. Under ultrasonic oscillation and high-speed stirring, the epoxy resin and the curing agent are fully mixed and uniformly mixed, and vacuum-assisted resin transfer molding is used to compound the quartz fiber cloth with a uniform carbon nanotube array on the surface with epoxy resin to improve the interfacial bonding strength with the quartz fiber, thereby improving the interlaminar shear strength of the quartz fiber carbon nanotube / epoxy resin composite material.

[0006] Chen Wenping and others invented a modified quartz fiber and its surface modification method. The surface modification method grows a layer of spherical nano-silicon dioxide on the surface of the quartz fiber, and the morphology of the nano-silicon dioxide layer is controllable. The nano-silicon dioxide layer effectively improves the surface roughness, specific surface area and silicon grafting rate of the fiber, and can improve the bonding strength of the organic-inorganic interface in the fiber pile through the dual effects of physical anchoring and chemical bonding at the interface of the two phases, thereby improving the mechanical strength, water resistance and service life of the composite material.

[0007] The above existing technologies are mainly aimed at the modification methods of quartz fiber in medium and low temperature environments, and there are few studies on the interface modification of quartz fiber under high and ultra-high temperature conditions. Therefore, based on the demand for high temperature resistant resin-based wave-transparent composite materials, it is necessary to carry out research on high temperature interface enhancement of quartz fiber reinforced composite materials. Summary of the invention

[0008] In view of the above problems, the present invention proposes a method for improving the high-temperature interface strength of quartz fiber reinforced resin-based composite materials from the perspective of improving the mechanical riveting of the interface, which is mainly to solve the problems of poor interface compatibility between fibers and resins of quartz fiber reinforced resin-based composite materials, low interface strength and easy damage under high temperature conditions, reduced mechanical properties of composite materials and weak structural stability.

[0009] The technical solution adopted by the present invention is as follows:

[0010] A method for improving the high temperature interface strength of a quartz fiber reinforced resin-based composite material is achieved by the following steps:

[0011] The first step is to clean the quartz fiber;

[0012] The second step is to activate the surface of the quartz fiber:

[0013] The third step is to perform grafting treatment on the surface of the activated quartz fiber;

[0014] The fourth step is to use the grafted quartz fiber and the resin matrix to form a composite material to obtain a quartz fiber reinforced resin matrix composite material.

[0015] Furthermore, the activation treatment is chemical etching, chemical grafting, plasma treatment or irradiation treatment.

[0016] Further, the grafting process includes:

[0017] preparing silicone resin solution;

[0018] Immerse the quartz fiber cloth in the silicone resin solution, take it out after a certain period of time, drain the excess silicone resin solution, spread it flat on the release paper, leave it for a certain period of time, rinse it and drain it;

[0019] The drained quartz fiber cloth is placed in a high temperature resistant film or mold, and grafted according to the set temperature and time.

[0020] Furthermore, the preparation of the silicone resin solution includes: dissolving silicone resin in a solvent to obtain the silicone resin solution, wherein the mass fraction of the silicone resin is 0.5% to 5%.

[0021] Furthermore, the immersion time is 0.5 to 2 hours; and the placement time on the release paper is 1 to 5 hours.

[0022] Furthermore, ethanol is used for the washing, and the washing times are 1 to 3 times.

[0023] Furthermore, the set temperature and time include: treating at 200-250° C. for 0.5-4 h, and then treating at 350-400° C. for 0.5-2 h, to obtain surface-grafted quartz fibers.

[0024] Furthermore, the resin matrix is ​​phenolic resin, polyimide resin, polyarylacetylene resin, phthalonitrile resin, etc.

[0025] Furthermore, the composite material is formed by molding, vacuum bag, autoclave or RTM, and the quartz fiber reinforced resin-based composite material is prepared by high-temperature curing molding.

[0026] A quartz fiber reinforced resin-based composite material prepared by the method.

[0027] The beneficial effects of the present invention compared with the prior art are as follows:

[0028] (1) The present invention can effectively improve the surface roughness and specific surface area of ​​quartz fiber by grafting silicone resin and forming a high-temperature resistant silicone resin cured product through post-treatment, increase the contact area with the resin matrix, and enhance the interface bonding ability between the fiber and the resin matrix through mechanical riveting, thereby improving the mechanical properties of the composite material.

[0029] (2) The present invention adopts silicone resin grafted quartz fiber, and the post-processed silicone resin solid has the characteristics of high temperature resistance and non-decomposition, and has strong high temperature retention ability. At the same time, the mechanical riveting reinforcement form under high temperature conditions has little instability on the interface bonding strength of the composite material, so it can effectively improve the high temperature mechanical properties of the composite material.

[0030] (3) The present invention is simple and easy to operate, suitable for large-scale processing, etc., and has high economic value in improving the high temperature resistance and application of quartz fiber reinforced resin-based composite materials.

[0031] (4) The present invention is suitable for the preparation of large-sized, complex-structured, high-temperature-resistant composite material products. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The figure is a flow chart of the steps of the method of the present invention. DETAILED DESCRIPTION

[0033] The present invention is described in detail below with reference to specific examples and accompanying drawings.

[0034] The present invention Figure 1 As shown, a new method for improving the high temperature interface of quartz fiber composite material is achieved according to the following steps:

[0035] 1. Cleaning quartz fiber

[0036] The fiber cleaning method adopts known techniques, such as acetone, ethanol, xylene, toluene, ethyl acetate and other solvent heating cleaning methods, high temperature treatment methods, and ultrasonic cleaning and other known methods to remove sizing agents and oil stains on the fiber surface. Those skilled in the art determine the corresponding cleaning method based on existing means.

[0037] 2. Fiber surface activation treatment

[0038] The surface activation of quartz fiber can be carried out by chemical etching, chemical grafting, plasma treatment or irradiation treatment. This process mainly improves the surface activity of the fiber and increases the content of polar groups. Those skilled in the art can determine the corresponding surface activation method based on existing means.

[0039] 3. Fiber surface grafting treatment

[0040] 3.1. Prepare silicone resin solution: dissolve silicone resin in a corresponding solvent, wherein the mass fraction of silicone resin in the silicone resin solution is 0.5% to 5%.

[0041] 3.2. Fiber surface grafting treatment: immerse the quartz fiber cloth in the silicone resin solution, take it out after immersion for 0.5 to 2 hours, drain the excess resin solution, spread it on the release paper, leave it for 1 to 5 hours, and then rinse it with ethanol 1 to 3 times. Then place the drained quartz fiber cloth in a high-temperature resistant film or mold, treat it at 200 to 250°C for 0.5 to 4 hours, and then treat it at 350 to 400°C for 0.5 to 2 hours to obtain surface-grafted quartz fiber.

[0042] 4. Composite material molding

[0043] The surface-grafted quartz fiber obtained in step 3.2 is used as a reinforcing material, and the resin matrix includes but is not limited to phenolic resin, polyimide resin, polyaryl acetylene resin, phthalonitrile resin, etc. The quartz fiber-reinforced resin-based composite material is prepared by high-temperature curing molding using common material molding methods such as molding, vacuum bag, autoclave or RTM.

[0044] Example 1: 0.28 mm quartz fiber reinforced polyimide resin composite material

[0045] 1. Clean the quartz fiber.

[0046] Use acetone to clean the quartz fiber. Place the quartz fiber in a fiber cleaning device, add acetone to cover the fiber, seal the cleaning device, connect condensation water and heated circulating water, control the temperature to 56°C, treat for 24 hours, take out, rinse with acetone, and place in a fume hood to remove the acetone.

[0047] 2. Activation of quartz fiber surface.

[0048] Treat the quartz fiber with nitric acid solution. Prepare a 40%wt nitric acid solution, immerse the quartz fiber in the solution, soak it at 25℃ for 2h, then take it out and rinse it with distilled water until the pH is greater than 6.0. Treat the activated quartz fiber at 100℃ for 2h and seal it for storage.

[0049] 3. Quartz fiber surface grafting treatment

[0050] 3.1. Prepare silicone resin solution: dissolve Dow Corning 0805 silicone resin in xylene solvent, and the mass fraction of the resin solution is 1%;

[0051] 3.2. Fiber surface grafting treatment: immerse the quartz fiber cloth in step 2 in the silicone resin solution, take it out after immersion for 2 hours, drain the excess resin solution, spread it on the release paper, leave it for 5 hours, and then rinse it again with ethanol twice. Then place the drained quartz fiber cloth in a high-temperature resistant film or mold, treat it at 200℃ for 0.5h and at 380℃ for 1h to obtain surface-grafted quartz fiber.

[0052] 4. Composite material molding

[0053] Quartz fiber reinforced polyimide composites were prepared by compression molding: a polyimide resin solution with a mass fraction of 40% was prepared, and a prepreg was prepared according to a mass ratio of resin: quartz fiber = 40:60, and then the solvent was removed. 20 prepregs were cut into 300mm×300mm pieces, aligned and laid in the female mold, and placed in a press for curing after the mold was closed. The curing system was 330℃ / 2h→350℃ / 2h→380℃ / 2h→400℃ / 1h, and then cooled to room temperature for demoulding.

[0054] After testing, the properties of the quartz fiber reinforced polyimide resin composite material prepared by the above method and the unmodified composite material are shown in Table 1. It can be seen that the bending strength of the sample treated by the present invention is increased by 43% and the interlaminar shear strength is increased by 35.2% compared with the unmodified sample.

[0055] Table 1 Properties of quartz fiber reinforced modified polyimide resin composites

[0056]

[0057] Example 2: 0.14 mm quartz fiber reinforced phenolic resin composite material

[0058] 1. Clean the quartz fiber.

[0059] Use acetone to clean the quartz fiber. Place the quartz fiber in a fiber cleaning device, add acetone to cover the fiber, seal the cleaning device, connect condensing water and heated circulating water, control the temperature to 56°C, treat for 24 hours, take out, rinse with acetone, and place in a fume hood to remove the acetone.

[0060] 2. Activation of quartz fiber surface.

[0061] Use silane coupling agent KH-550 solution to treat quartz fiber. Prepare 2%wt KH550 ethanol solution, immerse the quartz fiber in the solution, soak at 50℃ for 5h, take it out and rinse it with distilled water 3 times. Then place it in a 120℃ oven for 2h. Take it out and seal it for storage.

[0062] 3. Quartz fiber surface grafting treatment

[0063] 3.1. Prepare silicone resin solution: dissolve Zhonglan Chenguang 805 silicone resin in xylene / acetone mixed solvent, and the mass fraction of the resin solution is 3%;

[0064] 3.2. Fiber surface grafting treatment: immerse the quartz fiber cloth in step 2 in the silicone resin solution, take it out after immersion for 0.5 hours, drain the excess resin solution, spread it on the release paper, leave it for 3 hours, and then rinse it again with ethanol for 3 times. Then place the drained quartz fiber cloth in a high-temperature resistant film or mold, treat it at 250℃ for 2 hours, and treat it at 350℃ for 2 hours to obtain surface-grafted quartz fiber.

[0065] 4. Composite material molding

[0066] The quartz fiber reinforced phenolic resin composite material was prepared by vacuum bag molding: a phenolic resin solution with a mass fraction of 40% was prepared, and a prepreg was prepared according to the mass ratio of resin: quartz fiber = 50:50, and then the solvent was removed. The prepreg was cut into 20 pieces according to the size of 300mm×300mm, aligned and laid in the mold, and high-temperature vacuum auxiliary materials were laid. The curing system was 150℃ / 2h→180℃ / 2h→200℃ / 2h→250℃ / 2h, and it was cooled to room temperature and demolded.

[0067] After testing, the properties of the quartz fiber reinforced phenolic resin composite material prepared by the above method and the unmodified composite material are shown in Table 2. It can be seen that the bending strength of the sample treated by the present invention is increased by 60.5% and the interlaminar shear strength is increased by 62.5% compared with the unmodified sample.

[0068] Table 2 Properties of quartz fiber reinforced phenolic resin composites

[0069]

[0070] Example 3: 0.2 mm quartz fiber reinforced polyarylacetylene resin composite material

[0071] 1. Clean the quartz fiber.

[0072] Use acetone to clean the quartz fiber. Place the quartz fiber in a fiber cleaning device, add acetone to cover the fiber, seal the cleaning device, connect condensing water and heated circulating water, control the temperature to 56°C, treat for 24 hours, take out, rinse with acetone, and place in a fume hood to remove the acetone.

[0073] 2. Activation of quartz fiber surface.

[0074] The quartz fiber is treated with plasma. The quartz fiber is treated with air plasma, with an output power of 100W and a treatment time of 2min. After treatment, the quartz fiber is immediately sealed and vacuumed for storage or immediately proceeded to step 3.2.

[0075] 3. Quartz fiber surface grafting treatment

[0076] 3.1. Prepare silicone resin solution: dissolve the homemade HT-02 silicone resin in cyclohexane solvent, and the mass fraction of the resin solution is 2%;

[0077] 3.2. Fiber surface grafting treatment: immerse the quartz fiber cloth in step 2 in the silicone resin solution, take it out after immersion for 2 hours, drain the excess resin solution, spread it on the release paper, leave it for 4 hours, and then rinse it again with ethanol for 3 times. Then place the drained quartz fiber cloth in a high-temperature resistant film or mold, treat it at 250℃ for 2 hours and at 400℃ for 1 hour to obtain surface-grafted quartz fiber.

[0078] 4. Composite material molding

[0079] Quartz fiber reinforced polyarylidine resin composite material was prepared by RTM molding: 20 pieces of quartz cloth were cut into 200mm×600mm size, aligned and laid in the mold, and the mold was sealed. The injection temperature was 95℃ and the injection pressure was 0.25MPa. The curing system was 120℃ / 2h→150℃ / 2h→180℃ / 2h→210℃ / 2h→230℃ / 2h→250℃ / 2h, and the mold was demolded after cooling to room temperature.

[0080] After testing, the properties of the quartz fiber reinforced polyaryl acetylene resin composite material prepared by the above method and the unmodified composite material are shown in Table 3. It can be seen that the bending strength of the sample treated by the present invention is increased by 59.8% and the interlaminar shear strength is increased by 73.5% compared with the unmodified sample.

[0081] Table 3 Properties of quartz fiber reinforced polyaryl acetylene resin composites

[0082]

[0083] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.

Claims

1. A method for improving the high temperature interface strength of a quartz fiber reinforced resin-based composite material, characterized in that: The following steps are involved: Cleaning quartz fibers; Activate the surface of quartz fiber; Grafting treatment is performed on the surface of the activated quartz fiber; The grafted quartz fiber and the resin matrix are used to form a composite material to obtain a quartz fiber reinforced resin matrix composite material.

2. The method according to claim 1, characterized in that The activation treatment is chemical etching, chemical grafting, plasma treatment or radiation treatment.

3. The method according to claim 1, characterized in that The grafting process comprises: preparing silicone resin solution; Immerse the quartz fiber cloth in the silicone resin solution, take it out after a certain period of time, drain the excess silicone resin solution, spread it flat on the release paper, leave it for a certain period of time, rinse it and drain it; The drained quartz fiber cloth is placed in a high temperature resistant film or mold, and grafted according to the set temperature and time.

4. The method according to claim 3, characterized in that The preparation of the silicone resin solution comprises: dissolving silicone resin in a solvent to obtain the silicone resin solution, wherein the mass fraction of the silicone resin is 0.5% to 5%.

5. The method according to claim 3, characterized in that: The immersion time is 0.5 to 2 hours; the placement time on the release paper is 1 to 5 hours.

6. The method according to claim 3, characterized in that: The washing is performed with ethanol, and the number of washing times is 1 to 3 times.

7. The method according to claim 3, characterized in that The set temperature and time include: treating at 200-250° C. for 0.5-4 hours, and then treating at 350-400° C. for 0.5-2 hours, to obtain surface-grafted quartz fibers.

8. The method according to claim 1, characterized in that The resin matrix is ​​one of phenolic resin, polyimide resin, polyarylacetylene resin and phthalonitrile resin.

9. The method according to claim 1, characterized in that: The composite material is formed by molding, vacuum bag, autoclave or RTM molding method, and the quartz fiber reinforced resin-based composite material is prepared by high-temperature curing molding.

10. A quartz fiber reinforced resin-based composite material prepared according to the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Modified quartz fiber / cyanate ester composite material, and preparation method and applications thereof

    CN110156989A

  • Low-temperature wear-resistant anti-adhesion carbon fiber reinforced resin-based friction material and preparation method thereof

    CN114806075A

  • Quartz fiber reinforced silicon resin composite material capable of improving high-temperature interface strength and preparation method of quartz fiber reinforced silicon resin composite material

    CN117362695A

  • Modification method and application of quartz fiber

    CN118619564A

  • Surface modification method of quartz fiber

    CN1785874A